2015
DOI: 10.5811/westjem.2014.10.19488
|View full text |Cite
|
Sign up to set email alerts
|

Routine Repeat Head CT may not be Indicated in Patients on Anticoagulant/Antiplatelet Therapy Following Mild Traumatic Brain Injury

Abstract: IntroductionEvaluation recommendations for patients on anticoagulant and antiplatelet (ACAP) therapy that present after mild traumatic brain injury (TBI) are controversial. At our institution, an initial noncontrast head computed tomography (HCT) is performed, with a subsequent HCT performed six hours later to exclude delayed intracranial hemorrhage (ICH). This study was performed to evaluate the yield and advisability of this approach.MethodsWe performed a retrospective review of subjects undergoing evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…The results of our study, with only one clinically significant case of delayed intracranial hemorrhage (0.3% in the repeat CT group, 0.1% in total), support other investigations which concluded that a routine repeat CT is not necessary for patients with antithrombotic therapy, due to the low clinical significance of most detected DIH [27,28,29,30,31,32]. The single case of a clinically significant DIH in our study showed an altered neurological status and would therefore have received an additional CT during the observation period regardless of clinical protocol for routine repeat CT.…”
Section: Discussionsupporting
confidence: 88%
“…The results of our study, with only one clinically significant case of delayed intracranial hemorrhage (0.3% in the repeat CT group, 0.1% in total), support other investigations which concluded that a routine repeat CT is not necessary for patients with antithrombotic therapy, due to the low clinical significance of most detected DIH [27,28,29,30,31,32]. The single case of a clinically significant DIH in our study showed an altered neurological status and would therefore have received an additional CT during the observation period regardless of clinical protocol for routine repeat CT.…”
Section: Discussionsupporting
confidence: 88%
“…Most of these analyses have considered limited panels of ACAP medications and have not addressed patients taking multiple ACAP medications. Even in cases where a DICH is detected, neurosurgical operative intervention has been shown to be infrequent [ 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented in the literature that being on Warfarin therapy does present genuine immediate increased risk of intracranial bleed in patients with head injuries. 6,7 Some studies suggest as many as 17% of such patients can present with an intracranial bleed 2,6,8 and American College of Emergency Physicians guidelines recommend an immediate initial head CT. 7 Reviews of the literature on delayed bleed rates, however, reveal that this phenomenon is inconsistently tracked or studied. 5,7,9,10 In fact, the results of previous studies have suggested that bleeds of this type may occur days to weeks after initial injury.…”
Section: Discussionmentioning
confidence: 99%